Azide as an oxidant in the cathodic reaction of bioelectrochemical systems (BESs). Issue 117 (11th November 2015) - Zhou, Xiangtong; Qu, Youpeng; Kim, Byung Hong; Du, Yue; Li, Da; Liu, Jia; Feng, Yujie
Abstract : Azide could be an oxidant at the abiotic cathode of a BES, where it accepts electrons from acetate oxidation at the anode. Electron balance demonstrated that azide reduction was an eight electron reaction, with ammonia as the only product. Abstract : Azide could be used as an oxidant in the cathodic reaction in BESs, and produced a peak current of 0.37 mA. An estimation based on electron balance showed that azide reduction at the abiotic cathode was an eight-electron reaction, with NH3 as the only reduction product.